2011
DOI: 10.1210/jc.2011-0225
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the Girl with Early Onset of Pubic Hair

Abstract: Premature pubarche, or the development of pubic hair before the age of 8 in girls or 9 in boys, is most commonly caused by premature adrenarche. Adrenarche is the maturation of the adrenal zona reticularis in both boys and girls, resulting in the development of pubic hair, axillary hair, and adult apocrine body odor. Although originally thought to be a benign variant of normal development, premature adrenarche has been associated with insulin resistance and the later development of metabolic syndrome and polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 79 publications
1
30
0
5
Order By: Relevance
“…Hence, it is reasonable to hypothesize that altered gonadotropin secretory profiles could impact the cardinal features of PCOS, including hyperandrogenism and ovulatory dysfunction [3, 4]. In fact, increased circulating LH levels, increased LH:FSH ratios, elevated LH pulse frequency and/or amplitude, as well as relatively decreased FSH levels have been typically described in women with PCOS [3, 65].…”
Section: A Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is reasonable to hypothesize that altered gonadotropin secretory profiles could impact the cardinal features of PCOS, including hyperandrogenism and ovulatory dysfunction [3, 4]. In fact, increased circulating LH levels, increased LH:FSH ratios, elevated LH pulse frequency and/or amplitude, as well as relatively decreased FSH levels have been typically described in women with PCOS [3, 65].…”
Section: A Pathophysiologymentioning
confidence: 99%
“…Further, the early onset of adrenarche may represent the initial clinical feature of PCOS for some girls [4]. By the time patients present for medical attention, this multisystem disorder often has become a self-perpetuating derangement in which identification of initiating factors are difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It is primarily characterized by ovulatory dysfunction and hyperandrogenism (1,2), but the clinical presentation is heterogeneous and patients may present some of various signs and symptoms (Table 1). This heterogeneity seems to be modulated by multiple factors, such as prenatal androgen exposure, nutritional status in the uterus, genetic factors, as well as ethnicity, insulin resistance of puberty and/or exaggerated adrenarche and changes in body weight (4)(5)(6). Environmental factors, such as obesity, appear to exacerbate the underlying genetic predisposition.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of CYP17A1 in the adrenal reticular region leads to an increase levels of DHEA [24]. A study has demonstrated the increased size of the adrenal reticular band and increased in normal adolescent P450c17α activity to increase the synthesis of DHEA, which is onset of premature adrenal function to the process of PCOS [25]. The adrenal androgens have feedback effect on increasing the hypothalamic secretion of LH, which, in turn, leads to increase the synthesis of ovarian androgen.…”
Section: Adrenal Dysfunctionmentioning
confidence: 99%